Sandwich - The 'Completest Medieval Town in England' A Study of the Town and Port from its Origins to 1600 - Clarke, Helen (Historic England, 2010)
To the casual visitor of today, Sandwich appears as simply a small inland market town on the bank of a modest river. But locals and historians have long known that in the Middle Ages it was a strategic and commercial seaport of great significance, trading with northern Europe and the Mediterranean and growing prosperous on this business. The medieval fabric of the town has been preserved to a remarkable extent, but historians and archaeologists have never agreed on quite where the first settlement was located. Nor has there been close study of what the surviving medieval buildings can tell us about Sandwich's development. As well as providing a great amount of detail on the houses, churches and defences of medieval Sandwich, the authors apply the material evidence in order to draw out important social, economic and cultural facets in the evolution of the town. Maps, plans and photographs, all in full colour, supplement the text and graphically underline many of the conclusions.